Removal of Chromium (VI) by a Magnetic Nanoscale Zerovalent Iron–Assisted Chicken Manure-Derived Biochar: Adsorption Behavior and Synergetic Mechanism - Fang, Shengqiong; Huang, Xiaoyi; Xie, Shuangling; Du, Jiale; Zhu, Jianlong; Wang, Kai; Zhuang, Qinglin; Huang, Xuan (Frontiers in Bioengineering and Biotechnology, 2022)
Using chicken manure as raw material to prepare activated carbon as a dispersant, a novel biochar-loaded nano-zerovalent iron composite (nZVI@CMBC) was developed and applied to remove hexavalent chromium, i.e., Cr(VI), in wastewater. The dispersion of nano-zerovalent iron (nZVI) particles on the surface of chicken manure–derived biochar (CMBC) successfully inhibited the aggregation of magnetic iron particles and effectively reduced the size of nZVI particles. The results demonstrated that under acidic conditions, the removal efficiency of Cr(VI) by the nZVI@CMBC composite could reach 124.12 mg g−1. The pseudosecond-order kinetic model had a good agreement with the adsorption kinetics of the nZVI@CMBC composite, implying that the adsorption of Cr(VI) is based on the multi-layer chemical adsorption. Therefore, this study provides a new clue and strategy for removing Cr(VI) in wastewater.